2021
DOI: 10.4236/wjet.2021.93047
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Microstructures and Pin-on-Disc Wear Properties of 1010 Steel-Based and B<sub>4</sub>C-Added Materials Produced through Powder Metallurgy

Abstract: The present study makes use of two distinct production methods. The first method involves producing 1010 steel-based materials containing SiC, MgO, H 3 BO 3 , and B 4 C (wt%10 -wt%30) with varying weights through powder metallurgy. This step was followed by hot pressing. In the second group, after all the chemicals were stirred, 20 ml of epoxy and epoxy hardener were added to the mixture. Then, the mixture was set aside to harden. XRD and SEM-EDS analyses were conducted on the mixture to observe the morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…The main reason for this at the relevant wear load was thought to be the formation of lubricating oxide compounds during the wear test according to the B 4 C addition. Same observations were reported in the literature that there was a decrease in the friction coefficients generally depending on the B 4 C content [37,47]. Because it was reported that the B 2 O 3 compound was formed as a result of the contact of the B 4 C with air during wear tests.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The main reason for this at the relevant wear load was thought to be the formation of lubricating oxide compounds during the wear test according to the B 4 C addition. Same observations were reported in the literature that there was a decrease in the friction coefficients generally depending on the B 4 C content [37,47]. Because it was reported that the B 2 O 3 compound was formed as a result of the contact of the B 4 C with air during wear tests.…”
Section: Discussionsupporting
confidence: 79%
“…It must be stressed that the decrease in peak intensities in the XRD results due to B 4 C addition and thus the decrease in crystallinity was not supported by the SEM results due to liquid phase sintering. A similar sintering effect due to the production method was reported on the Silicon Nitride films, implant materials of 316L and 1010 steel-based materials containing SiC, MgO, H 3 BO 3 and varying B 4 C amounts in [36,37,40] respectively.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations